Ectomycorrhizal fungi are shared between seedlings and adults in a monodominant Gilbertiodendron dewevrei rain forest in Cameroon. (24th November 2016) - Michaëlla Ebenye, Helvyne C.; Taudière, Adrien; Niang, Nogaye; Ndiaye, Cheikh; Sauve, Mathieu; Awana, Nérée Onguene; Verbeken, Mieke; De Kesel, André; Séne, Seynabou; Diédhiou, Abdala G.; Sarda, Violette; Sadio, Omar; et al.
Abstract: Ectomycorrhizal networks may facilitate the establishment and survival of seedlings regenerating under the canopies of tropical forests and are often invoked as a potential contributor to monodominance. We identified ectomycorrhizal fungi in a monodominant Gilbertiodendron dewevrei (Fabaceae) rain forest in Cameroon, using sporocarps and ectomycorrhizae of three age categories (seedlings, intermediate trees, and large trees) and tentatively revealed nutrient transfer through ectomycorrhizal networks by measuring spontaneous isotopic ( 13 C and 15 N) abundances in seedlings. Sporocarp surveys revealed fewer ectomycorrhizal fungal taxa (59 species from 1030 sporocarps) than molecular barcoding of ectomycorrhizal roots (75 operational taxonomic units from 828 ectomycorrhizae). Our observations suggest that ectomycorrhizal fungal diversity is similar to that in other mixed tropical forests and provide the first report of the Tuber ‐ Helvella lineage in a tropical forest. Despite some differences, all age categories of G. dewevrei had overlapping ectomycorrhizal fungal communities, with families belonging to Thelephoraceae, Russulaceae, Sebacinaceae, Boletaceae, and Clavulinaceae. Of the 49 operational taxonomic units shared by the three age categories (65.3% of the ectomycorrhizal fungal community), 19 were the most abundant on root tips of all categories (38.7% of the shared taxa), supporting the likelihood of ectomycorrhizal networks. However, we obtained no evidence for nutrient transfer from trees to seedlings. We discuss the composition of the ectomycorrhizal fungal community among the G. dewevrei age categories and the possible role of common ectomycorrhizal networks in this rain forest.